THE IMPACT OF EUROPEAN YOUTH BASKETBALL LEAGUE (EYBL) ON THE DEVELOPMENT OF THE U16 MEN’S BASKETBALL TEAMS - Dara , Lilla Csenge; Bácsné Bába, Éva (Stadium - Hungarian Journal of Sport Sciences, 2021)
The main focus of our research was the U16 age group since it is one of the most significant in terms of the young athlete’s future - probably professional - career. It was very helpful in research that this age group was a priority in the Basketball Academy of Debrecen’s program and they were competing in an international basketball league, in the European Youth Basketball League (EYBL). Thanks to the EYBL tournaments we have got a chance to analyze this youth category completely. For primer research we have chosen three teams, two Hungarian, and one Italian, to get an impression why is so important to play basketball at the international level in this age.  We have made interviews with the coaches, organizers and the manager of the league to have an international comparison of this age group.